Understanding Sources of Suffering and Pathways to Healing in Mi’kmaq Communities - Obomsawin, Anik; Muir, Lucille; Fiocco, Alexandra Jasmine (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2025)
Despite enduring a range of atrocities, Mi’kmaq people continue to be resilient in the face of adversity. In collaboration with the Union of Nova Scotia Mi'kmaq and through discussions with eight Knowledge Holders, this research aimed to uncover sources of suffering and healing pathways in Mi’kmaq communities. Knowledge Holders identified salient sources of suffering including residential schooling and past policies, ongoing systemic discrimination, collective loss, and community conflict. Knowledge Holders emphasized the importance of engaging in wholistic healing practices that are grounded in Mi’kmaq culture, spirituality, and ways of knowing. Similarly, strengthening connections to culture, community, ancestors, and the land was described as a healing pathway. This research provides support for community-based services that promote healing through cultural revitalization.